Tan Malaka, Sosio Intelektual-Religi Sang Pejuang Revolusioner dan Relevansinya dengan Pendidikan Islam - Syafrizal, Syafrizal; Sesmiarni, Zulfani (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
As Tan Malaka knows, he is a materialist thinker who is a Marxist, presumably because of his materialistdialectical style of thinking (a la Marx) this labeling of atheism was then also addressed to a noble child named Sutan Datuk Ibrahim by public understanding. Apart from the public image above, the background of Tan Malaka, who grew up in the Islamic Minangkabau land, is certainly not something that can be simply forgotten. Evidently, even though he has traveled far and explored various styles of thought, the Islamic style is still strongly reflected in his thoughts. Her life background of being raised in a devout family seems to have succeeded in stealing a trace of her mind's attention. thought is formed in socio-intellectual religion and its relevance to Islamic education